The Representation of Sexism in the Novel Cantik Itu Luka and Its Translation: Gender Analysis, Appraisal, and Translation Techniques - Wikanditha, Kennia (The Future of Education Journal, 2024)
This study discusses the representation of sexism in Eka Kurniawan's novel Cantik Itu Luka and its English translation, focusing on gender issues, appraisal analysis, and translation techniques. Using a qualitative descriptive method, the research analyzes sexist utterances categorized according to Mansour Fakih’s theory of gender injustice, and examines the translation techniques based on Molina and Albir’s theory. The results show that sexism in the novel appears in various forms, such as stereotypes, marginalization, and subordination, represented through the characters' utterances and the author's narrative. The translation analysis reveals shifts in meaning influenced by the translator’s choices in adjusting evaluative lexis in the target language to achieve acceptability, while still maintaining fidelity to the source text. This study emphasizes the importance of integrating appraisal theory into translation practice to ensure contextual equivalence and sensitivity to gender issues.